Border Shifts: New Mobilities in Europe and Beyond - Ribas-Mateos, N. (Palgrave Macmillan, 2020)
Border Shifts develops a more complex and multifaceted understanding of global borders, analysing internal and external EU borders from the Mediterranean region to the US-Mexico border, and exploring a range of issues including securitization, irregular migration, race, gender and human trafficking